The fascinating world of mayenite (Ca12Al14O33) and its derivatives - Adriano Intiso; Federico Rossi; Antonio Proto; Raffaele Cucciniello (Rendiconti Lincei. Scienze Fisiche e Naturali, 2021)
Mayenite (12CaO·7Al 2 O 3 ) is a mesoporous calcium aluminum oxide, with a characteristic crystalline structure. The framework of mayenite is composed of interconnected cages with a positive electric charge per unit cell that includes two molecules [Ca 24 Al 28 O 64 ] 4+ , and the remaining two oxide ions O 2− , often labelled “free oxygen”, are trapped in the cages defined by the framework. Starting from mayenite structure several derivatives have been prepared through advanced synthetic protocols by free oxygen substitution with various anions. Mayenite and its derivates have been intensively investigated in many applications which include catalysis (oxidation and reduction, ammonia synthesis, pinacol coupling), environmental sensors and CO 2 sorbent materials. In this review, we summarize our recent results on the main applications of mayenite and its derivatives.

Use of Zea mays L. in phytoremediation of trichloroethylene - Emanuele Moccia; Adriano Intiso; Angela Cicatelli; Antonio Proto; Francesco Guarino; Patrizia Iannece; Stefano Castiglione; Federico Rossi (Environmental Science and Pollution Research, 2017)